Decentralized and distributed active fault diagnosis: Multiple model estimation algorithms - Straka, Ondřej; Punčochář, Ivo (Zielona Góra: Uniwersytet Zielonogórski)
The paper focuses on active fault diagnosis (AFD) of large scale systems. The multiple model framework is considered and two architectures are treated: the decentralized and the distributed one. An essential part of the AFD algorithm is state estimation, which must be supplemented with a mechanism to achieve feasible implementation in the multiple model framework. In the paper, the generalized pseudo Bayes and interacting multiple model estimation algorithms are considered. They are reformulated for a given model of a large scale system. Performance of both AFD architectures is analyzed for different combinations of multiple model estimation algorithms using a numerical example.
Keywords: fault diagnosis; large scale systems; multiple models